Exploring the Link between Generalised Ligament Laxity and Flexible Flatfoot in Paediatric and Adolescent Populations: A Case-control Study - Ashish Yadav; Shalu Arimbooth; Avinash Muraleedharan; Shweta Chaubey (Journal of Clinical and Diagnostic Research)
Introduction: Flatfoot, or pes planus, is a postural deformity resulting from the inadequate development of the Medial Longitudinal Arch (MLA) of the foot. Generalised ligament laxity is the most important aetiological factor among various predisposing factors. Previous research has explored these conditions independently rather than investigating their potential association. This study focuses on understanding how generalised ligament laxity contributes to flexible flatfoot, which could provide valuable insights that have not been thoroughly explored in paediatric and adolescent populations. Aim: To determine the association between flexible flatfoot and generalised ligament laxity in paediatric and adolescent populations. Materials and Methods: This case-control study was conducted on 180 patients attending the Physical Medicine and Rehabilitation (PMR) Outpatient Department (OPD), aged 5 to 19 years, from September 2019 to March 2021. Footprints were taken from the subjects and a flatfoot assessment was performed using Staheli’s plantar arch index. The Jack test was conducted in all flatfoot subjects to exclude rigid flatfoot. All patients with flexible flatfoot were enrolled as cases, while those without flatfoot were enrolled in the control group. Both groups were further evaluated using the Beighton Score for the presence of generalised ligament laxity and results were recorded. Demographic factors were expressed as frequencies, and quantitative data were presented as median with 25th and 75th percentiles (IQR=interquartile range). Differences in qualitative variables between the groups were analysed using the Chi-square test. Results: Out of the 180 subjects, 126 (70%) were male, and the majority, 108 (60%), were aged 11 to 19 years, with a mean ± SD age of 11.46±3.1 years. The proportion of ligament laxity was higher in cases 30 (41.67%) than in controls 20 (18.52%), and this association was statistically significant (p-value=0.016). Patients with flatfoot had a 3.14 times higher chance of having ligament laxity than those lacking flatfoot, which was statistically significant. Conclusion: Children and adolescents with increased generalised ligament laxity are more predisposed to the development of flexible flatfoot compared to those without ligament laxity.